Professional development: Then and now - Bolt, Susan (IADIS Press, 2012)
Technological developments have altered pedagogies in classroom teaching but approaches to teacher professional development have remained largely unchanged. The purpose of this paper is to describe an evolving learning process that spans the last decade and draws from three different investigations into professional development. One study was situated in a face-to-face action research context and the other in an online environment. The conclusions drawn about the nature of effective professional development in these independent studies show that whether in online or face-to-face contexts educational developers need to consider similar elements. A review of the literature indicated that further research was required to enhance the development, implementation and evaluation of online professional development opportunities to meet the in-time learning needs of teachers in sustainable ways. The author concludes by summing up the advantages and disadvantages of moving towards online teacher professional development and considers possible applications.